2016
DOI: 10.1007/s12035-016-9934-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesizing Music Intervention Enhances Brain Functional Connectivity Involving Dopaminergic Recruitment: Common Neuro-correlates to Abusable Drugs

Abstract: The goal of this review is to explore the clinical significance of music listening on neuroplasticity and dopaminergic activation by understanding the role of music therapy in addictive behavior treatment. fMRI data has shown that music listening intensely modifies mesolimbic structural changes responsible for reward processing (e.g., nucleus accumbens [NAc]) and may control the emotional stimuli’s effect on autonomic and physiological responses (e.g., hypothalamus). Music listening has been proven to induce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 52 publications
(55 reference statements)
2
12
0
Order By: Relevance
“…This would be consistent with the evidence of alterations in the functional limbic circuits involved in the processing of emotional information in anorexia nervosa [50]. A previous reports suggests that, in healthy subjects, musical stimuli produce an intense activation of the reward system at the limbic level [51]. Recent evidence ascribes this action to the recruitment of the accumbens nuclei [52], an area involved in the pathogenesis of affective manifestations of patients with AN [53].…”
Section: The Baseline Differences In N100 Latency and The Musical Effsupporting
confidence: 88%
“…This would be consistent with the evidence of alterations in the functional limbic circuits involved in the processing of emotional information in anorexia nervosa [50]. A previous reports suggests that, in healthy subjects, musical stimuli produce an intense activation of the reward system at the limbic level [51]. Recent evidence ascribes this action to the recruitment of the accumbens nuclei [52], an area involved in the pathogenesis of affective manifestations of patients with AN [53].…”
Section: The Baseline Differences In N100 Latency and The Musical Effsupporting
confidence: 88%
“…13 Physiological studies have demonstrated increased limbic activity in the orbitofrontal cortex and alterations in mesolimbic dopamine release on functional MRI (fMRI) in response to music. 14 In HD, music may have the potential to address abnormal movements as well as quality-of-life issues that arise from the loss of expressive and communicative skills, especially in advanced disease.…”
Section: Resultsmentioning
confidence: 99%
“…These alterations may, in turn, lead to a reduction in the central pain sensitization and hyperalgesia associated with OA [ 166 168 ]. For example, emerging evidence suggests that both meditation and ML can induce beneficial changes in central nervous system dopaminergic and other neurochemical systems [ 169 171 ] and enhance autonomic regulation, in part by modulating activation of the sympathoadrenal system and HPA axis and by increasing parasympathetic dominance [ 165 , 172 , 173 ]. In addition, recent controlled trials of ML and meditation suggest these practices can alter activity, increase grey matter density and/or volume, and promote functional connectivity in multiple brain areas involved in the cognitive, affective, and sensory processing of pain, including the periaqueductal grey matter, hippocampus, prefrontal cortex, insula, amygdala, orbitofrontal cortex, thalamus, somatosensory cortex, and anterior cingulate gyrus [ 157 , 158 , 163 165 , 172 , 174 180 ].…”
Section: Discussionmentioning
confidence: 99%